2019
DOI: 10.1098/rspb.2018.2542
|View full text |Cite
|
Sign up to set email alerts
|

Sexual ornaments but not weapons trade off against testes size in primates

Abstract: Males must partition their limited reproductive investments between traits that promote access to females (sexual ornaments and weapons) and traits that enhance fertilization success, such as testes and ejaculates. Recent studies show that if the most weaponized males can monopolize access to females through contest competition, thereby reducing the risk of sperm competition, they tend to invest less in sperm production. However, how males invest in sexual ornaments relative to sperm production remains less cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 78 publications
0
27
1
Order By: Relevance
“… * References are [1] Lüpold et al, 2019 , [2] Thorén et al, 2006 , [3] Gomendio et al, 2011 , [4] Harcourt et al, 1995 , [5] Lüpold, 2013 , [6] Anderson et al, 1999 , [7] Dixson and Anderson, 2004 , [8] Taylor and Schwitzer, 2011 , [9] Mittermeier et al, 2013 , [10] Soulsbury, 2010 . **or Hapalemur griseus or H. alaotrensis ***or multimale, see Soulsbury, 2010 .…”
Section: Resultsmentioning
confidence: 99%
“… * References are [1] Lüpold et al, 2019 , [2] Thorén et al, 2006 , [3] Gomendio et al, 2011 , [4] Harcourt et al, 1995 , [5] Lüpold, 2013 , [6] Anderson et al, 1999 , [7] Dixson and Anderson, 2004 , [8] Taylor and Schwitzer, 2011 , [9] Mittermeier et al, 2013 , [10] Soulsbury, 2010 . **or Hapalemur griseus or H. alaotrensis ***or multimale, see Soulsbury, 2010 .…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with inter-specific analyses that have shown that species with lower levels of direct male-male competition do not exhibit strong trade-offs between investment in weaponry and investment in testis volume 10 but contrasts with intra-specific studies of other taxa, which have clearly demonstrated trade-offs between traits that are involved in pre- and post-copulatory competition 31,32,62 . This finding may also reflect different patterns of investment in canines and testes: once canines are formed, no additional energetic investment is required – in contrast, testes need to be maintained throughout adult life 12 . We would need many data points collected across the lifespan of individual males in order to test this idea.…”
Section: Discussionmentioning
confidence: 99%
“…8 ). Furthermore, there is evidence for trade-offs between traits related to pre-copulatory selection (e.g., ornaments and weaponry) and post-copulatory selection (testis volume and ejuaculates) 912 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Parker’s seminal paper 50 years ago [ 3 ], the existence of post-copulatory sexual selection has also been acknowledged, with mechanisms ranging from altering the duration of copulation, to altering the amount of parental care provided, depending on characteristics of the copulation partner [ 4 , 5 ]. More recently still, research has begun to examine the interaction between the pre-copulatory episode of sexual selection that culminates in copulation and the post-copulatory episode that culminates in fertilizing the egg [ 6 , 7 , 8 , 9 , 10 , 11 ]. If the two episodes work synergistically, they can strengthen overall selection; or if they work in opposing directions, the action of one episode may diminish the strength of selection in the other episode [ 9 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%